Answer:
Solution is
![y(t)=C_1e^x+C_2xe^x+(x^3e^x)/(6)](https://img.qammunity.org/2020/formulas/mathematics/college/b5rjav3jsuew5rjz4t8b7upm2m4mivo41b.png)
Explanation:
Given Differential Equation,
...............(1)
We need to solve the given differential equations using undetermined coefficients.
Let the solution of the given differential equation is made up of two parts. one complimentary solution and one is particular solution.
![\implies\:y(x)=y_c(x)+y_p(x)](https://img.qammunity.org/2020/formulas/mathematics/college/348jkmvt6wfb070l0s0gyd5odr8vrpmwil.png)
For Complimentary solution,
Auxiliary equation is as follows
m² - 2m + 1 = 0
( m - 1 )² = 0
m = 1 , 1
So,
![y_c(x)=C_1e^x+c_2xe^x](https://img.qammunity.org/2020/formulas/mathematics/college/peg5gc5uyb9foc3lh70rvn5275ow90zv50.png)
Now for particular solution,
let
![y_p(x)=Ax^3e^x](https://img.qammunity.org/2020/formulas/mathematics/college/a4r73dkql6hqklymows372zidut3ocva8a.png)
![y'=Ax^3e^x+3Ax^2e^x](https://img.qammunity.org/2020/formulas/mathematics/college/ujioe7sjvne5c7rq3rdjspfqfkaneoselg.png)
![y](https://img.qammunity.org/2020/formulas/mathematics/college/ym5u67caxkgdl7nhly9xg4gd9l0ry2is9q.png)
Now putting these values in (1), we get
![Ax^3e^x+6Ae^2e^x+6Axe^x-2(Ax^3e^x+3Ax^2e^x)+Ax^3e^x=xe^x](https://img.qammunity.org/2020/formulas/mathematics/college/vhy8l63oyvi4brwhj1v1gej9wy4u297bei.png)
![Ax^3e^x+6Ae^2e^x+6Axe^x-2Ax^3e^x-6Ax^2e^x+Ax^3e^x=xe^x](https://img.qammunity.org/2020/formulas/mathematics/college/b3l4hbmacciyizdbyzcyvsuqxcadsaws0s.png)
![6Axe^x=xe^x](https://img.qammunity.org/2020/formulas/mathematics/college/n0djaf9nj0q2zuzy9kknoll35i0c4uosa8.png)
![6A=1](https://img.qammunity.org/2020/formulas/mathematics/college/lmo5srfo2v462ck7iiw9kf0uvv9sexaqq4.png)
![A=(1)/(6)](https://img.qammunity.org/2020/formulas/mathematics/college/n0ydx44iyb5112d74bsv4e3y204lozwm1v.png)
![\implies\:y_p(x)=(x^3e^x)/(6)](https://img.qammunity.org/2020/formulas/mathematics/college/36n6mmc250hpcotmkqtzfctiditgx4k2ym.png)
Therefore, Solution is
![y(t)=C_1e^x+C_2xe^x+(x^3e^x)/(6)](https://img.qammunity.org/2020/formulas/mathematics/college/b5rjav3jsuew5rjz4t8b7upm2m4mivo41b.png)